Role of Computed Tomography Pulmonary Angiogram in Patients with History of Shortness of Breath and Deep Vein Thrombosis (Journal of Fatima Jinnah Medical University, 2024)
Background: Computed tomography pulmonary angiography (CTPA) is vital for detecting pulmonary embolism (PE) arising from deep vein thrombosis (DVT) and presenting with shortness of breath. This study aimed to establish CTPA diagnostic role in patients with breathlessness and DVT risk factors, accurately detecting PE and associated vascular abnormalities, thus improving patient outcomes.Patients and methods: This retrospective study was conducted at Department of Radiology, Ittefaq Hospital Lahore over four months. The patient aged over 16-45 with 28 females and 48 males who had a history of DVT and shortness of breath were part of research. CTPA was including performed with bolus tracking. Data was collected after filling consent form, including the duration from onset of symptoms such as leg pain, swelling, chest pain and shortness of breath. Radiologists categorized CT images to report PE findings. Statistical analysis utilized descriptive statistics to describe basic features and chi-square test was used to compare the dependent groups. The p-value less than 0.05 was considered as statistically significant.Results: , bronchiectasis (40.8%), unilateral PE (39.5%), consolidation (39.5%), and ground glass opacity (35.5%).Conclusion: ConclusivelyCTPA's diagnostic utility was evident, identifying PE in a significant proportion with associated findings like bilateral involvement and vascular abnormalities. It provided crucial information for timely PE diagnosis and management in patients with shortness of breath and predisposing DVT risk factors.
Keywords: Pulmonary embolism; CT pulmonary angiography; deep vein thrombosis